Improved Cultivation Practices for soybean - Dass, Anchal; Rishiraj, Rishiraj; Vyas, A. K.; Kumar, Sanjeev (Indian Farming, 2016)
Soybean (Glycine max) has acquired first place in area andproduction among oilseed crops in India. It is grown on more than 10 million hectare area. Soybean is highly nutritive (40% protein, 20% oil) and also enriches soil by virtue of fixing atmospheric nitrogen. It is potential source of food, feed and also has industrial use. Thus, soybean has been looked upon as a reliable alternative to high water demanding rice crop in the non-conventional areas like Indo-Gangetic plains. There has been skeptism about its large scale adoption in this rice-dominated region due to presumed low yields and non-availability of remunerative market prices. However, with adoption of improved cultivars and agronomic practices, soybean yield could be as high as 2.5 t/ha and net returns 54,571 with B: C ratio of 2.26, which are comparable to rice.